Neuroadaptive saturated control for relative motion based noncooperative spacecraft proximity with prescribed performance. (March 2021) - Xia, Kewei; Zou, Yao
Abstract: This paper investigates the control issue of the noncooperative spacecraft proximity with prescribed performance by exploiting only relative motion information. To accommodate the direct use of relative measurement, the 6-degree-of-freedom (6DOF) relative dynamics is formulated in the body frame of the pursuer. Based on the smooth Gauss error function, a new asymmetric saturation function is developed to satisfy the practical control limitations. To maintain the relative attitude and position within specified constrained ranges, a novel performance function in possession of the preassigned settling time and convergence set of steady state error is proposed. Based on the backstepping framework, the relative attitude and position controllers are surveyed in sequence. In particular, a state constrained virtual control is first developed for each relative dynamics by introducing a nonlinear transformation. Then a neuroadaptive saturated control law is designed by implementing a Nussbaum function based adaptive control coefficient. Stability analysis indicates that the closed-loop 6DOF relative dynamics are asymptotically stable with prescribed performance. Numerical simulations further verify the proposed control strategy. Highlights: A control strategy is developed by using only relative motion information. A novel performance function with accurate and intuitive settling time is proposed. An asymmetric saturation function is designed to satisfy the control constraints. A neuroadaptive algorithm is introduced to ensure the high control accuracy.